Studi Perencanaan Bangunan Pelengkap Pada Boezem Di Kelurahan Blimbing Kota Malang - Fitriyasari, Ammy; Andawayanti, Ussy; Cahya, Evi Nur (Fakultas Teknik, Universitas Brawijaya, 2021)
The area of Blimbing Village is one of the areas of Malang City where often having flood in rainy season. The flood in the Blimbing Village area is caused by the inadequacy of the existing drainage and also not using water absorption building or Boezem effeciently, therefore need some effort to overcome this problem. One of the solution to tackel this problem is make use boezem more efficiently, in order to reduce flood. In the analysis results of design discharge of the study area was obtained for 3.970 m3/ sec for the two years period and 4,606 m3/ sec for five years period. In order to reduce flood at the study area, an alternative flood control is implemented. The alternative is to increase the storage capacity of the Boezem and planned support buildings specifically planning drainage channels, and planning for inlet and outlet of sluice gates. There are alternative, it can reduce flood by 30%. Based on the results of the analysis, it is obtained that the design budget (RAB) for support buildings planning according to the main unit price for the activities of the city of Malang is IDR 146,620,000.